2015
DOI: 10.1080/21645515.2015.1061159
|View full text |Cite
|
Sign up to set email alerts
|

iVAX: An integrated toolkit for the selection and optimization of antigens and the design of epitope-driven vaccines

Abstract: Computational vaccine design, also known as computational vaccinology, encompasses epitope mapping, antigen selection and immunogen design using computational tools. The iVAX toolkit is an integrated set of tools that has been in development since 1998 by De Groot and Martin. It comprises a suite of immunoinformatics algorithms for triaging candidate antigens, selecting immunogenic and conserved T cell epitopes, eliminating regulatory T cell epitopes, and optimizing antigens for immunogenicity and protection a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 67 publications
(68 reference statements)
0
82
0
Order By: Relevance
“…We found that immune response to T cell epitopes was inversely correlated with their degree of cross-reactivity with the human genome in a subsequent study of H7N9 peptides [43]. Examining more than 4,000 published human T cell epitopes (from the Immune Epitope Database, IEDB, http://www.iedb.org/), we recently determined that the JanusMatrix "homology" score is significantly higher (p<0.0001) for T cell epitopes shown to induce regulatory cytokine (IL-10) response (N=3,780 epitopes), and significantly lower (p<0.01) for T cell epitopes shown to induce effector cytokine (IL-4) response (N=1,433 epitopes) [14]. Thus large-scale analysis of published T cell epitopes in public databases has provided additional confirmation for the hypothesis that epitope-redundancy deviate the phenotype of T cell-mediated immune responses.…”
Section: Improving Computational Tools To Identify Epitope Redundancymentioning
confidence: 99%
See 2 more Smart Citations
“…We found that immune response to T cell epitopes was inversely correlated with their degree of cross-reactivity with the human genome in a subsequent study of H7N9 peptides [43]. Examining more than 4,000 published human T cell epitopes (from the Immune Epitope Database, IEDB, http://www.iedb.org/), we recently determined that the JanusMatrix "homology" score is significantly higher (p<0.0001) for T cell epitopes shown to induce regulatory cytokine (IL-10) response (N=3,780 epitopes), and significantly lower (p<0.01) for T cell epitopes shown to induce effector cytokine (IL-4) response (N=1,433 epitopes) [14]. Thus large-scale analysis of published T cell epitopes in public databases has provided additional confirmation for the hypothesis that epitope-redundancy deviate the phenotype of T cell-mediated immune responses.…”
Section: Improving Computational Tools To Identify Epitope Redundancymentioning
confidence: 99%
“…Most T cell epitope mapping tools evaluate the amino acid sequence of each input 9-mer peptide (derived from the set of overlapping 9-mer sequences in any protein antigen) to a set of binding coefficients that define the propensity of the sequence to bind to HLA. On an overall scale, proteins carrying more putative epitopes would expected to be more immunogenic while proteins carrying fewer putative epitopes would tend to be less immunogenic [14]. On a local scale, T-cell epitopes (class II-restricted in particular) are not randomly distributed throughout protein sequences but instead tend to "cluster" in specific regions, and are known as promiscuous T cell epitopes [52].…”
Section: Epitope Mapping Using Computational Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…iVAX is an integrated set of tools for triaging candidate antigens, selecting immunogenic and conserved T cell epitopes, eliminating regulatory T cell epitopes, and optimizing antigens for immunogenicity and protection against disease [187]. iVAX has been applied to vaccine development programs for emerging infectious diseases, cancer antigens and biodefense targets.…”
Section: Other Methods For Immunogenicity Predictionmentioning
confidence: 99%
“…2 Rose et al discuss the choice of the adjuvant during vaccine design and demonstrate that while the adjuvants do increase the innate response in mice injected with piggyBac plasmids, no adjuvant increases the level of transfection of the antigen. 3 Moise et al 4 describes the iVAX suite of tools along with their applications for the design of vaccines for Tularemia, Smallpox, H. Pylori, Burkholderia, HCV, Lassa virus or H1N1 and H7N9. Eickhoff et al describe the immunoinformatic strategy and in vivo validation of the identification of 30 epitopes that could be used in the design of Chagas disease vaccine.…”
mentioning
confidence: 99%